Laser stimulated light reflection for TeO2-WO 3-Bi2O3 thin films with incorporated Si nanoparticles - Kassab, L. P R [UNESP]; Camilo, M. E.; De Assumpção, T. A A; Myronchuk, G. L. (Elsevier, 2013)
A novel method of preparation of the Si nanoparticles (NPs) incorporated in tellurite TeO2-WO3-Bi2O3 (TWB) thin films is proposed. This mew method applies RF magnetron sputtering technique at room temperature. The incorporation of Si NP was confirmed by transmission electron microscopy (TEM); isolated Si NPs with diameters of around 6 nm are observed. Energy dispersive X-ray spectroscopy (EDS) was performed during TEM analysis in order to confirm the presence of Si NP and also the other elements of the thin film. The thin films are explored with respect to the photoinduced changes of the reflectivity within the 400-65 nm spectra range using a 10 ns pulsed Nd:YAG with power densities varying up to 400 MW/cm2 and beam diameter within the 3-5 mm range. The observed processes are analyzed within a framework of trapping level conceptions for the Si NP. The possible application of the discovered materials as optical sensitive sensors is proposed. © 2013 Elsevier B.V.
Keywords: Optical features of nanoparticles; Photoinduced optical effects; Energy dispersive X ray spectroscopy; Optical effects; Optical features; Photoinduced change; RF magnetron sputtering technique; Room temperature; Sensitive sensors; Transmission electron microscopy (TEM); Light reflection; Magnetron sputtering; Nanoparticles; Tellurium compounds; Thin films; Transmission electron microscopy; X ray spectroscopy; Silicon